Characterization of Cellulosic Leaf Fiber from the Typha Angustifolia Plant - Govardhana Rao Chilukoti; Ramesh Naidu Mandapati (Journal of Natural Fibers, 2022)
Typha leaves are a rich source of fiber cables and these fibers can also be extracted by chemical retting method and these are easily bio-degradable, and eco-friendly. The main objective of present work is to assess the fiber characteristics such as FTIR, XRD, TGA, SEM, and single fiber tensile properties by varying fiber extraction parameters. In the retting process, IR peaks clearly shows that there was a removal nonfibrous material (NFM). Using X-ray diffraction technique 67.61% crystallinity with a crystallinity index of 0.521 was observed. Fiber tips of SEM images confirm that by increase in chemical concentration and treatment time, there was more removal of NFM and fibrillation found. For the fiber extraction mainly two treatment particulars were varied i.e. sodium hydroxide (10, 20, and 30 gpl) and time (3, 4, 5, and 6 h). Out of various retting conditions, at 20 gpl with 4 and 5 h treatment time shows an excellent tensile strength of single fiber, i.e. 125 Mpa and 179.82 Mpa and 30 gpl with 4 hrs and 5 h observed moderate strength, i.e. 106.03 Mpa and 122.69 Mpa respectively.